Dari Masa ke Masa: Sejarah Perkembangan Masjid Baiturrohmah di Lahat - Yuma; Hudaidah (Nazharat: Jurnal Kebudayaan, 2025)
This article discusses the history and strategic role of the Baiturrohmah Mosque in Lahat, South Sumatra, as a religious, social, and cultural center for the local community. Established around 1930, the mosque was originally a simple building born from the religious spirit of the still-growing Muslim community. Over time, the mosque underwent various stages of renovation and development, especially in 2001 and 2007, to accommodate the increasing number of worshipers and the needs of religious activities. More than just a place of worship, the Baiturrahmah Mosque is now a center for Islamic education, social activities, and a space for community deliberation. The active role of community leaders and the spirit of mutual cooperation are the main keys in maintaining the existence and sustainability of the function of this mosque. This article emphasizes that the Baiturrohmah Mosque is a spiritual and social symbol that reflects the strength of the community in building a civilization based on Islamic values.